Naturally acquired Rift Valley fever virus neutralizing antibodies predominantly target the Gn glycoprotein - Wright, D.; Allen, E.R.; Clark, M.H.A.; Gitonga, J.N.; Karanja, H.K.; Hulswit, R.J.G.; Taylor, I.; Biswas, S.; Marshall, J.; Mwololo, D.; Muriuki, J.; Bett, Bernard K.; et al. (Elsevier, 2020)
Rift Valley fever (RVF) is a viral hemorrhagic disease first discovered in Kenya in 1930. Numerous animal studies have demonstrated that protective immunity is acquired following RVF virus (RVFV) infection and that this correlates with acquisition of virus-neutralizing antibodies (nAbs) that target the viral envelope glycoproteins. However, naturally acquired immunity to RVF in humans is poorly described. Here, we characterized the immune response to the viral envelope glycoproteins, Gn and Gc, in RVFV-exposed Kenyan adults. Long-lived IgG (dominated by IgG1 subclass) and T cell responses were detected against both Gn and Gc. However, antigen-specific antibody depletion experiments showed that Gn-specific antibodies dominate the RVFV nAb response. IgG avidity against Gn, but not Gc, correlated with nAb titers. These data are consistent with the greater level of immune accessibility of Gn on the viral envelope surface and confirm the importance of Gn as an integral component for RVF vaccine development.